Synthesis and characterization of cationic gemini surfactant modified Na–bentonite and its applications for rubber nanocomposites. Issue 2 (27th May 2015) - Khalaf, A.I.; Hegazy, M.A.; El‐Nashar, D.E.
Abstract : A cationic gemini surfactant ( N ‐isopropyl‐ N, N ‐dimethyldodecan 1‐aminium bromide) was synthesized by quaternization reaction. The synthesized surfactant was characterized by Fourier transform infrared (FTIR) and proton nuclear magnetic resonance (1H NMR) spectroscopy. Modified Na–bentonite (organoclay) was obtained by the intercalation of a gemini surfactant between the layers of sodium bentonite and characterized by X‐ray diffraction (XRD), transmission electron microscopy (TEM), FTIR, thermogravimetry–differential thermal analysis (TGA–DTA) and differential scanning calorimetry (DSC) techniques. The results of XRD, TEM, FTIR, TGA, and corresponding DSC analysis indicate that gemini surfactant has been successfully intercalated into the clay layers. Rubber‐based nanocomposites have been prepared by incorporating various concentration of organically modified bentonite on to natural rubber/styrene–butadiene rubber (NR/SBR) rubber blend (75/25) using two roll mill. Effect of organoclay content on XRD, curing, mechanical, and scanning electron microscopy (SEM) properties of the nanocomposites are investigated. The morphological study showed the intercalation of nanoclay in NR/SBR blend chain. It was found that the organoclay decrease the optimum and scorch time of the curing reaction, increase maximum torque and the curing rate, which was attributed to the further intercalation during vulcanization process. Mechanical properties such as tensile strength, modulus and elongation at break have improved. POLYM. COMPOS., 38:396–403, 2017. © 2015 Society of Plastics Engineers